2001
DOI: 10.1016/s0168-6496(01)00130-1
|View full text |Cite
|
Sign up to set email alerts
|

PCR-SSCP comparison of 16S rDNA sequence diversity in soil DNA obtained using different isolation and purification methods

Abstract: This study compared different methods of direct DNA extraction and purification from a silt loam soil and investigated the relationship between DNA quantity and sequence diversity. Five extraction methods and four purification techniques were investigated. Quantities of DNA extracted were between 3.4 þ 0.55 and 54.3 þ 8.18 Wg g 31 (dry wt) of soil with OD 260 /OD 230 purity ratios between 0.80 and 1.15. Analysis of sequence diversity in all extracts was conducted using PCR-single strand conformation polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…These primers hybridize to phylogenetically highly conserved regions within the 16S rRNA gene and amplify products that contain the two variable regions, V4 and V5. These regions were found useful for PCR-SSCP analyses of bacterial communities in several other studies [21,38,39]. PCR with total DNA of all chosen Collembola species yielded products of the expected size (368-375 bp).…”
Section: Sscp-profiles From Different Collembolamentioning
confidence: 85%
“…These primers hybridize to phylogenetically highly conserved regions within the 16S rRNA gene and amplify products that contain the two variable regions, V4 and V5. These regions were found useful for PCR-SSCP analyses of bacterial communities in several other studies [21,38,39]. PCR with total DNA of all chosen Collembola species yielded products of the expected size (368-375 bp).…”
Section: Sscp-profiles From Different Collembolamentioning
confidence: 85%
“…This finding has been confirmed by molecular methods which have shown that the majority of microbial species, including the predominant species, are not represented in culture collections (Tindall, 2004). On the other hand, metagenomic studies may also be prone to bias which can be introduced by differences in DNA extraction (Stach et al, 2001), as well as PCR bias due to differences in primer binding (Hansen et al, 1998) or sequence heterogeneity (Suzuki et al, 1998). The main limitation of both metagenomic and traditional culturebased techniques is that one is unable to determine what role each phylotype performs within a specific ecological niche.…”
Section: Introductionmentioning
confidence: 81%
“…Numerous studies have been done to ascertain the most suitable DNA extraction and purification protocol from soil (e.g. Wikström et al 1996;Jackson et al 1997;Cullen and Hirsch 1998;Bürgmann et al 2001;Miller 2001;Stach et al 2001;Kauffmann et al 2004), but comparison of the results showed a number of inconsistencies. Extraction methods ranged from liquid nitrogen grinding (Volossiouk et al 1995), microwave-based rupture (Orsini and Romano-Spica 2001), enzymatic lysis (Zhou et al 1996;Stach et al 2001), to bead beating lysis (Miller et al 1999;Bürgmann et al 2001).…”
Section: Introductionmentioning
confidence: 99%